Audit Culture: Why Law Journals are Ranked and What Impact This Has on the Discipline of Law Today - Kathy Bowrey (Legal Education Review)
In this article we map the history of important changes in Australian legal education over the past 20 years, with a focus on the influence of the profession on legal education. Using Thornton’s account of contemporary law schools ‘jettisoning the critical’ as a starting point we sketch out a vision of legal education that retains a strong focus on critical thinking. We also ask what spaces for critical pedagogy might be created and argue that even in the context of current constraints it is possible for legal academics to teach in ways that are consonant with their values and pedagogical philosophies. As evidence of this, we set out some of the ways that we are undertaking this project in our own compulsory and elective courses at the Adelaide Law School.